2017
DOI: 10.1038/ncomms14954
|View full text |Cite
|
Sign up to set email alerts
|

Global site-specific N-glycosylation analysis of HIV envelope glycoprotein

Abstract: HIV-1 envelope glycoprotein (Env) is the sole target for broadly neutralizing antibodies (bnAbs) and the focus for design of an antibody-based HIV vaccine. The Env trimer is covered by ∼90N-linked glycans, which shield the underlying protein from immune surveillance. bNAbs to HIV develop during infection, with many showing dependence on glycans for binding to Env. The ability to routinely assess the glycan type at each glycosylation site may facilitate design of improved vaccine candidates. Here we present a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
288
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(311 citation statements)
references
References 90 publications
(199 reference statements)
17
288
2
Order By: Relevance
“…Recent studies using chromatography coupled mass spectrometry analysis of soluble Env proteins, suggested that the N156 glycan position is occupied largely by a high mannose glycan (Behrens et al, 2016; Panico et al, 2016). Another study (Cao et al, 2017) indicated that N156 is occupied either by high mannose or complex glycans for several soluble SOSIP.664 trimers, including the CRF250 trimer used in this study. Further studies are required to fully understand the compositions of the glycans in the V2 apex region on different isolates and expressed from different cell types.…”
Section: Resultsmentioning
confidence: 83%
“…Recent studies using chromatography coupled mass spectrometry analysis of soluble Env proteins, suggested that the N156 glycan position is occupied largely by a high mannose glycan (Behrens et al, 2016; Panico et al, 2016). Another study (Cao et al, 2017) indicated that N156 is occupied either by high mannose or complex glycans for several soluble SOSIP.664 trimers, including the CRF250 trimer used in this study. Further studies are required to fully understand the compositions of the glycans in the V2 apex region on different isolates and expressed from different cell types.…”
Section: Resultsmentioning
confidence: 83%
“…This study showed a very high occupancy level of recombinant gp120 N-glycosylation sites, however, the effect of metabolic engineering on protein occupancy during biosynthesis is unknown. A methodology to assess occupancy on a site-specific level has been developed and applied to various Env strains [79]. Here, protease-generated (glyco)peptides are first treated with Endo H and then digested with PNGase F in O 18 -water.…”
Section: Assessment Of Glycan Site Occupancymentioning
confidence: 99%
“…Cao et al , reported that almost all sites are more than 90 % occupied on soluble Env trimers of 6 different strains [79]. …”
Section: Assessment Of Glycan Site Occupancymentioning
confidence: 99%
See 1 more Smart Citation
“…Glycomics is the systematic study of glycan structures, including monosaccharide compositions, glycan sequence, branching pattern and linkage specifications, which are essential to the functions of glycoconjugates [1114]. Nevertheless, glycomics analysis is inherently challenging due to their structure complexity and heterogeneity, low natural abundance and the lack of amplification methods [5,14,15]. …”
Section: Introductionmentioning
confidence: 99%